Implementasi Program Pendaftaran Tanah Sistematis Lengkap (PTSL) Sebagai Upaya Percepatan Pendaftaran Tanah Di Badan Pertanahan Nasional Kabupaten Simalungun - Bethesda Simanjuntak; Rudi Kristian Manurung (UNIVED PRESS, Universitas Dehasen Bengkulu, 2023)
This study aims to find out and describe how the Implementation of the Complete Systematic Land Registration Program at the National Land Agency of Simalungun Regency. This research uses descriptive research method with a qualitative approach. Data collection techniques were carried out by interviews, observation and documentation to key informants and key informants involved in the implementation of the Complete Systematic Land Registration implementation program. The data obtained were then analyzed qualitatively by reviewing all of data supported by Van Meter and Van Horn theory which included policy standards and objectives, resources, characteristics of implementing agencies, implementor dispositions, communication between organizations, and the economic, social environment, politics. From the results of the study, the Implementation of the Complete Systematic Land Registration Program at the National Land Agency of Simalungun Regency was found to be running well even though the existing human resources or implementing personnel were still lacking in quantity. So that implementation both in the field and at the office must work with an inappropriate workload.